MATURITY AND ABILITY TO UNDERSTAND RIGHTS AND OBLIGATIONS TO COMPLY WITH LEGAL ACTION UNDER INDONESIAN CIVIL CODE - Amalia Khoerun Dwinisa (Problematika Hukum, 2021)
Civil law is the rulemaking of a person an internal legal entity, jurisdiction, and obligations in the exercise of rights and matters affecting jurisdiction. Law has a theme. Civil law subjects consist of natural persons and legal entities. All legal entities have rights and obligations when performing legal acts. The purpose of this paper is to examine under what conditions a person receives his rights and duties when performing juristic acts. This paper concludes that not everyone can exercise their rights and obligations in performing legal acts, and some exceptions prevent people from exercising their rights and obligations.Keywords: Keywords: rights and obligations, legal acts, civil law